2013
DOI: 10.1007/s10389-013-0578-3
|View full text |Cite
|
Sign up to set email alerts
|

The economic value of Quebec’s water fluoridation program

Abstract: AimDental caries is a major public health problem worldwide, with very significant deleterious consequences for many people. The available data are alarming in Canada and the province of Quebec. The water fluoridation program has been shown to be the most effective means of preventing caries and reducing oral health inequalities. This article analyzes the cost-effectiveness of Quebec’s water fluoridation program to provide decision-makers with economic information for assessing its usefulness.MethodsAn approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 20 publications
0
29
0
2
Order By: Relevance
“…The cost-effectiveness of water fluoridation has been recently assessed in Canada 97 and Australia, 98 and both studies suggested significant cost savings can be made as a result of water fluoridation, especially if a large population is covered by a scheme. We have a poor understanding of the cost-effectiveness of this public health intervention for the UK.…”
Section: A 2003 Cochrane Reviewmentioning
confidence: 99%
“…The cost-effectiveness of water fluoridation has been recently assessed in Canada 97 and Australia, 98 and both studies suggested significant cost savings can be made as a result of water fluoridation, especially if a large population is covered by a scheme. We have a poor understanding of the cost-effectiveness of this public health intervention for the UK.…”
Section: A 2003 Cochrane Reviewmentioning
confidence: 99%
“…The final ten studies were composed of nine peer-reviewed journal articles 5, 916 plus a report 17 . Geographically, six of the studies were from the U.S. 5, 911, 15, 17 , with the rest from Australia 13, 14 , Canada 16 , and New Zealand 12 .…”
Section: Evidence Synthesismentioning
confidence: 99%
“…Geographically, six of the studies were from the U.S. 5, 911, 15, 17 , with the rest from Australia 13, 14 , Canada 16 , and New Zealand 12 . Six papers 9, 1114, 16 provided cost and benefit information, two 13, 14 of which also conducted cost-effectiveness analysis using DALY. The remaining four papers 5, 10, 15, 17 provided only benefit information and used regression models to analyze the change in treatment cost or dental claims with the presence of CWF.…”
Section: Evidence Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…[123] A modelling study on CWF in South Africa also reported that benefits of CWF would exceed costs. [124] At least since the year 2000, there appear to be no published studies in the peer-reviewed literature that show that CWF is not costeffective (i.e., in communities over 1000 people and where the water is not naturally fluoridated).…”
Section: Health Inequalities and Cost Effectivenessmentioning
confidence: 99%